TYPES OF HEMOLYSIS OF GRAM-NEGATIVE BACTERIA ISOLATED FROM THE TONSILS OF WEANED LANDRACE PIGS - Novriansyah, Rizky; Suardana, I Wayan; Mahatmi, Hapsari (Buletin Veteriner Udayana, 2025)
The tonsils serve as the primary gateway for bacterial entry into the body and are part of the lymphatic system, which is rich in immune cells, particularly phagocytes. Various pathogenic bacteria can colonize the tonsils, including Gram-negative bacteria with high virulence potential. This study aims to identify and characterize Gram-negative bacteria from the mucosa of post-weaning pig tonsils based on their haemolysis properties. Samples were collected from three different farming locations, namely Selat Village, Sangeh Village, and Taman Giri, which have different environmental conditions such as housing type, humidity, and temperature. The methods used included Gram staining to determine bacterial morphological characteristics and haemolysis testing on blood agar to observe haemolysis patterns. The results showed that among 14 isolates tested, 50% (7/14) exhibited alpha-haemolysis, 36% (5/14) exhibited beta-haemolysis, and 14% (2/14) exhibited gamma-haemolysis. Based on these characteristics, the potential bacteria identified included Haemophilus sp., Pasteurella sp., Actinobacillus spp., and Escherichia coli, which exhibited different haemolytic abilities depending on their virulence factors. Environmental factors such as housing type, humidity, and temperature also influenced the haemolysis patterns of the bacteria. The variations in haemolysis patterns observed indicate differences in the expression of virulence factors among the bacteria colonizing the tonsils of post-weaning pigs from the three study locations.